Synchronous esophageal and lung cancer treated by one-stage esophagectomy and upper right lobectomy - Wójcik, Janusz; Grodzki, Tomasz; Kubisa, Bartosz; Pieróg, Jarosław; Wojtyś, Małgorzata; Bielewicz, Michał; Wójcik, Norbert (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
We present a case of 58 year-old patient with solid food dysphagia due to neoplastic infiltration of the esophagus 37 centimeters from the incisors and 10 kilograms body weight loss. Computed tomography revealed abnormal 20 mm thickness of the esophagus wall up to 5 cm above the cardia as well as enlarged 15 mm pericardial lymph node suspected of metastatic etiology. Diagnosis of adenocarcinoma was confirmed endoscopically. Gastroscopy and endoscopic ultrasound (EUS) examination were not possible to perform below the level of the esophageal infiltration stenosis. Bronchofiberoscopy revealed no pathological findings. The patient was treated by parenteral nutrition for 10 days prior to surgery. Ivory-Lewis esophageal resection was performed with two-field lymphadenectomy and thoracic duct resection. A tumor 1 cm in diameter located in the upper right lobe not found on chest computed tomography (CT) was palpated at the time of the surgery. It was decided to perform additional right upper lobectomy. Histopathological specimen examination confirmed primary synchronous small cell lung cancer. The role of PET examination in preoperative diagnosis of patients with esophageal cancer is discussed below.